Teong Negeri: Sakralitas Identitas Lokal Masyarakat Negeri Adat di Maluku Tengah - Salakory, Revaldo Pravasta Julian Mb (Paradigma: Jurnal Kajian Budaya, 2020)
This article discusses the sacredness of Teong Negeri in the life of the indigenous people in Maluku. Teong Negeri is seen as a symbol of the customary state in Central Maluku, among others, Negeri Haya, Hatu, Tehua and Wassu and has a function in maintaining the socio-cultural network. the four states of Pela Gandong Negeri Haya, Hatu, Tehua and Wassu use Teong Negeri as a daily greeting. It can be seen that Teong Negeri is a sacred symbol for the four states of pela gandong because in addition to being a symbol of identity that is able to integrate each other, but also a symbol of respect for ancestors. Based on research data related to the results of the interview Teong Negeri has to do with the history of the establishment of the state, in the life of indigenous people in Wassu state known as Teong Erihatu Samasuru, Haya state known as teong Nakajarimau, Hatu state known as Teong Silalou and Tehua state by the name of Teong Lounusa Amalatu. Ethnographic qualitative research methods are used to obtain in-depth field findings data, based on the informants' understanding of Teong Negeri as a sacred identity for the people of central Maluku in maintaining the cultural network (Islamic-Christian relations) during and after the conflict. So based on the findings, it can be seen that Teong Negeri is able to provide spirit capital for the entire community to keep alive the cultural provisions in the life of indigenous people in Central Maluku.